Risk of neurological, eye and ear disease in offspring to parents with schizophrenia or depression compared with offspring to healthy parents. Issue 16 (19th April 2018) - Gunnarsdóttir, Elin Dianna; Hällgren, Jonas; Hultman, Christina M; McNeil, Thomas F; Crisby, Milita; Sandin, Sven
Abstract: Background: Neurological, visual and hearing deviations have been observed in the offspring of parents with schizophrenia. This study test whether children to parents hospitalized with schizophrenia have increased the likelihood of childhood neurological disorder. Methods: Among all parents in Sweden born 1950–1985 and with offspring born 1968–2002: 7107 children with a parent hospitalized for schizophrenia were compared to 172 982 children with no parents hospitalized for schizophrenia or major depression, as well as to 32 494 children with a parent hospitalized for major depression as a control population with another severe psychiatric outcome. We estimated relative risks (RR) and two-sided 95% confidence intervals calculated from Poisson regression. Results: Children to parents with schizophrenia were more likely than controls to have been hospitalized before the age of 10 with a diagnosis of cerebral palsy, RR = 1.76 (95% CI: 1.15–2.69); epilepsy, RR = 1.78 (95% CI: 1.33–2.40), combined neurological disease, RR = 1.33 (95% CI: 1.11–1.60) and certain diseases of the eye, RR = 1.92 (95% CI: 1.17–3.15) and ear, RR = 1.18 (95% CI: 1.05–1.32). Similar disease-risk-pattern was found for children to parents hospitalized with a diagnosis of major depression. A specific risk increase for strabismus RR = 1.21 (95%CI: 1.05–1.40) was found for off-spring with parental depression. Conclusions: Compared with children to healthy parents, children to parents with schizophrenia have increased risk of a variety of neurological disorders as well as visual and hearing disorders at an early age. The risk increase was not specific to schizophrenia but was also seen in children to parents with a diagnosis of major depression.